Building the next generation of foreign policy professionals: One internship at a time. (December 2015) - Conley Tyler, Melissa; Rothnie-Jones, Olivia; McCambridge, Kate; Walsh, Eleanor
The future of foreign policy think tanks should involve acting as a training ground for the next generation of international affairs professionals. Internships are widely recognized as a way of improving young people's skills and employment prospects. A case study of the Australian Institute of International Affairs' (AIIA's) internship program shows how foreign policy institutes can form a bridge between the academic grounding that universities provide and the rigours and requirements of a career in international affairs. Survey results from more than 100 interns showed an overwhelmingly positive reaction to their internship experience, with over 98 percent recommending the program. A range of learning outcomes and career benefits were reported. Foreign policy institutes wishing to contribute to career development should consider introducing internship programs that include goal setting, high-quality supervision, expert training, and career advice. They can help build the future of the field one internship at a time.